PENINGKATAN PENGETAHUAN DAN PRAKTEK SISWA SD KELAS IV DAN V TENTANG CARA MENGGOSOK GIGI YANG BAIK DAN BENAR DENGAN MENGGUNAKAN MEDIA BUKU BERGAMBAR DI SDN 2 BAUMATA TIMUR - Pinat, Leny Marlina A.; Pay, Mery Novaria; Eluama, Merniwati Sherly; Burhan, Rofidah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Background: Dental and oral health is still a problem in society that needs attention. This is indicated by the prevalence of the population with dental and oral problems in Indonesia according to Riskesdas 2018, which has increased sharply from 23.2% in 2007 to 57.6% in 2018. Dental and oral health problems are still a major concern among elementary school children, especially due to the lack of knowledge and proper tooth brushing practices. Objective: This study aims to determine the effectiveness of picture book media in improving knowledge and proper tooth brushing practices in grades IV and V at SDN 2 Baumata Timur. Method: the method used is a quantitative approach with a pre-experimental one group pretest-posttest design. The sample in this study was 40 students selected by total sampling. Results: Data were collected through a knowledge questionnaire and observation sheets for tooth brushing practices before and after intervention in the form of providing picture books. The results of the study showed an increase in the knowledge score and practice of brushing students' teeth after using picture book media. The average knowledge score increased from 50 to 77.5, and the practice of brushing teeth showed a more appropriate behavioral change according to the recommended brushing standards. The conclusion of this study is that picture book media is effective as an educational tool to improve students' understanding and skills in maintaining dental and oral health. It is recommended that similar media be used continuously in health learning in elementary schools.